(untitled) (Third Sector Social Economic Review, 2026)
Today, the sub-dimensions of sustainability, namely environmental, social, and governance (ESG), and ESG practices, go beyond simply reflecting businesses’ sustainability approaches; they have significant impacts on numerous factors, including consumer preferences and market demands. Within this framework, the main objective of this study is to examine the impact of the ESG performance of companies included in the Borsa Istanbul Sustainability Index (XUSRD) on net sales, one of the key indicators of financial performance, over the period 2018–2022. Accordingly, panel data analysis is employed in the study. The results of the analysis reveal that firms’ overall ESG performance, as well as the environmental and social dimensions of ESG, have a positive and statistically significant effect on net sales.